2018
DOI: 10.11606/s1518-8787.2018052006258
|View full text |Cite
|
Sign up to set email alerts
|

Nascer no Brasil: a presença do acompanhante favorece a aplicação das boas práticas na atenção ao parto na região Sul

Abstract: OBJECTIVETo analyze if the presence of a companion favors the use of best practices in the delivery care in the South region of Brazil.METHODSThis is a cross-sectional analysis of the longitudinal study Nascer no Brasil. We analyzed data from 2,070 women from the South region of Brazil who went into labor. The data were collected between February and August 2011, by interviews and medical records. We performed a bivariate and multivariate analysis, calculating the crude and adjusted prevalence ratios using Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2
49

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 39 publications
7
51
2
49
Order By: Relevance
“…It is important to emphasize the importance of the companion in the delivery and birth process, a study carried out in southern Brazil, showing that the support of the companion is associated with best practices and movement, able to reduce the pain and duration of LA (31) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize the importance of the companion in the delivery and birth process, a study carried out in southern Brazil, showing that the support of the companion is associated with best practices and movement, able to reduce the pain and duration of LA (31) .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Obstetric Nursing in the institution was associated with non-performance of trichotomy when compared to institutions that did not have Obstetric Nursing. In 2014, a systematic review demonstrated that there is insufficient evidence to recommend perineal tricotomy for women on admission to LA (34) , since it does not influence better rates of infection, dehiscence of the perineal wound or other neonatal infections (31) .…”
Section: Discussionmentioning
confidence: 99%
“…13 The role of mediator is exercised when the companion is welcomed and encouraged to develop comfort actions, negotiating the parturient's wishes with the health team, as well as actively participating in the application of non-pharmacological methods of pain relief. 21 It is revealed in the third sub-category, "Respect for the rights of the accompanying person", that the participants stress the importance of their participation and of having their law respected by the institution and professionals:…”
Section: Resultsmentioning
confidence: 99%
“…25 It is exposed that the health institutions in Brazil that allow the presence of the companion are those that seek to reduce unnecessary interventions, and that have programmed changes in the ambience and in the furniture, such as having chairs for all the companions. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The organization of physical spaces is necessarily altered when a mode of attention to childbirth and birth is sought which privileges the privacy, dignity and autonomy of the woman when giving birth in a more welcoming and comfortable environment with the presence of companion. 24 The conditions of the environment for the humanization of births and births must comply with all these guidelines, as recommended in Resolution No.…”
Section: Motherhood Is a Race But I Felt Good Because I Had Roommentioning
confidence: 99%
“…Sua prevalência ainda é alta, chegando 15% no trabalho realizado por (MONGUILHOTT et al, 2018), que visava avaliar estatisticamente, como nascem os brasileiros em nosso serviço público. Nele, foi no inferido que apenas 34,8% das mães tiveram a presença de um acompanhante durante o parto, o que também é fator de sofrimento para a mãe.…”
Section: Musicoterapia No Parto Cesáreounclassified